A descriptive study on safety perception among ride-hailing car passengers in Malaysia - Shazwan Daud, Mohd; Osman, Syuhaily; Hashim, Ahmad Hariza; Abd Rahim, Husniyah (Human Resource Management Academic Research Society, 2023)
Recently, major ride-hailing car (RHC)-related safety issues have become more prevalent in Malaysia. Due to distracted driving, speeding, irregular working schedules and exposure to a various of unsafe road environment circumstances, road traffic accidents are extremely likely to happen to RHC drivers. Consequently, the aim of this study is to examine road safety perception among RHC passengers in Malaysia. There are six section in the questionnaire comprising respondents background, travel behaviour and pattern, safety perception, driving behaviour factors, vehicle safety factors and road environment factors. A convenient sampling was used and the sample comprised of 350 random RHC passengers. Descriptive statistical analysis revealed that a disagreement and neutral level of respondents for the questions asked especially for driving behaviour factors and vehicle safety factors. Nevertheless, the responses were generally around neutral and high agreement for the road environment factors. Based on the results, the findings of the study were also discussed.